Bovine Colostrum Before or After Formula Feeding Improves Systemic Immune Protection and Gut Function in Newborn Preterm Pigs - Li, Yanqi; Pan, Xiaoyu; Nguyen, Duc Ninh; Ren, Shuqiang; Moodley, Arshnee; Sangild, Per Torp (Frontiers in Immunology, 2020)
Objectives: Maternal milk is often absent or in limited supply just after pre-term birth. Many preterm infants are therefore fed infant formula as their first enteral feed despite an increased risk of feeding intolerance, necrotizing enterocolitis (NEC), and infection. Using preterm pigs as a model for preterm infants, we hypothesized that bovine colostrum given before or after formula feeding would alleviate formula-induced detrimental effects during the first days after preterm birth. Methods: A total of 74 preterm pigs received gradually increasing volumes of formula (F) or bovine colostrum (C) until d 5, when they were euthanized or transitioned to either C or F for another 4 days, resulting in six groups: C or F until d 5 (C5, F5, n=11 each), C or F until d 9 d (CC, FF n=12-13 each), C followed by F (CF, n=14), and F followed by C (FC, n=13). Results: Systemically, colostrum feeding stimulated circulating neutrophil recruitment on d 5 (C5 vs. F5, both P<0.05). Relative to initial formula feeding, initial colostrum feeding promoted the development of systemic immune protection as indicated by a decreased T helper cell population and an increased regulatory T cell population (CC+CF vs. FC+FF, both P<0.01). In the gut, colostrum feeding improved intestinal parameters such as villous heights, enzymes, hexose absorption, colonic goblet cell density, and decreased the incidence of severe NEC (27 vs. 64%), diarrhea (16 vs. 49%), and gut permeability on d 5, coupled with lowered expression of LBP, MYD88, IL8, HIF1A, CASP3 (C5 vs. F5, all P<0.05). On d 9, the incidence of severe NEC was similarly low across groups (15-21%), but diarrhea resistance and intestinal parameters were further improved by colostrum feeding, relative to exclusive formula feeding (CC, CF or FC vs. FF, respectively, all P<0.05). The expression of MYD88 and CASP3 remained down-regulated by exclusive colostrum feeding (CC vs. FF, all P<0.01) and colostrum before or after formula feeding regulated HIF1A and CASP3 expression marginally. Conclusion: Colostrum feeding ameliorated the detrimental effects of formula feeding in systemic immunity and gut health in preterm newborns, especially when given immediately after birth.